The prevalence and safety of direct oral anticoagulants in patients with non-atrial fibrillation associated intra-cardiac thrombus. (14th October 2021) - Kanwal, A; Zulty, M; Rao, S; Young, R
Abstract: Background: The standard of care in management of intra-cardiac thrombus has been the use of vitamin K antagonists (VKAs). The emergence and use of direct oral anticoagulants (DOACs) in other conditions has led to the consideration of their use in patients with intra-cardiac thrombus. Thus far, case-reports have provided the majority of data regarding the efficacy of DOACs in this population. Purpose: The aim of this observational study was to investigate the safety and efficacy of DOACs in intracardiac thrombus not associated with atrial fibrillation, compared to the current standard of care, VKAs. Methods: An observational study was conducted between 10 hospitals in our region. The study was conducted between 2013 and 2019 in patients with a diagnosis of intracardiac thrombus. All left and right, atrial and ventricular thrombi were included. Patients with atrial fibrillation were excluded. Patient information was collected from the hospital electronic record. The primary endpoints were clinically significant bleeding requiring transfusion and thromboembolic events, excluding myocardial infarction. Results: 1153 patients had a diagnosis of intracardiac thrombus. 878 out of 1153 patients were discharged on warfarin and 275 were discharged on a DOAC. In the warfarin population 73 of 878 patients (8.3%) had clinically significant bleeding events compared to 21 of 275 patients (7.6%) in the DOAC population (p=0.801). The median ages were 60.5 and 58 respectively. The median time period to a bleeding event was 151 and 198 days respectively. In the warfarin population, 116 of 878 patients (13.2%) had thromboembolic disease versus 34 of 275 patients (12.4%) in the DOAC arm (p=0.759). The median ages were 62 and 62.5 respectively. The median time period to a thromboembolic event was 114 and 184 days respectively. In the warfarin arm, 3 patients had systemic thromboembolism and 113 patients had embolic strokes. In the DOAC arm, 2 patients had systemic thromboembolism, 32 patients had embolic strokes. Conclusion: The data from this study suggests that DOACs may be a feasible alternative to warfarin in patients with intracardiac thrombus. There was no statistically significant difference in the rates of clinically significant bleeding or in incidence of thromboembolic disease. To our knowledge, this is the largest observational study to date on this topic. Randomized controlled trials are needed to fully establish the efficacy of DOACs in this patient population. Funding Acknowledgement: Type of funding sources: None.